The Effect of Accrual Earnings Management, Real Earnings Management, and Institutional Ownership on Leverage - Anita Anggraini; Eddy Suranta (Yayasan Ilomata, 2023)
The purpose of this research is to provide empirical evidence on the influence of accrual and real-based earnings management and institutional ownership on leverage. The dependent variable is leverage. The independent variables are accrual earnings management (DAC), real earnings management (CFO, PROD, DISEXP), and institutional ownership. This research uses multiple linear regression. The sample used is a manufacturing company listed on the Indonesian Stock Exchange and has an ESG score from 2018-2022. The sample for this research was selected using a purposive sampling technique with a total of 120 observation data. The results of this research show that earnings management using 4 proxies, namely accrued earnings management (DAC) and real earnings management (CFO, PROD, DISEXP) has a significant influence on leverage. Institutional ownership does not have a significant effect on leverage. The implications of this research are very large because it provides support for the application of agency theory. However, it is crucial to highlight that the scope of this research is confined to Indonesian manufacturing enterprises, therefore the conclusions may not be immediately transferable to other nations.